Maximizing bacterial survival: integrating sense-and-respond and bet-hedging mechanisms - Lowrey, Lillian C.; Gadda, Nicole C.; Tamayo, Rita (Trends in microbiology (Regular ed.), 2025)
Many bacteria have integrated mechanisms of phase variation (PV) and two-component systems (TCSs) to regulate phenotypes. We propose three integration schemes and explore how combining stochastic and deterministic regulation may enhance population-level fitness.In parallel integration, PV and a TCS independently regulate a gene/operon, allowing its expression to be decoupled from the TCS regulon – a benefit when the gene product is deleterious while the rest of the regulon remains adaptive.In PV-dominant integration, a TCS is subject to phase variation. This scheme allows binary control of the entire TCS regulon which may be beneficial when the regulon's effects are uniformly adaptive or detrimental.In TCS-dominant integration, a TCS controls phase variation. TCS activation may affect the directionality or rate of phase variation, tuning the level and dynamics of phenotypic heterogeneity. Two-component systems allow bacteria to respond to specific environmental signals with defined adaptive phenotypic changes, a process that requires time and may be inadequate for contending with rapidly changing environments. In contrast, phase variation generates baseline levels of phenotypic heterogeneity that helps to ensure survival of the population as a whole. This strategy may be better suited to confront abrupt environmental changes but may produce transiently less-fit subpopulations. Many bacteria have integrated phase variation and two-component signaling – how combining these stochastic and deterministic mechanisms affects bacterial fitness is unclear. Here, we identify three distinct schemes for integration of phase variation and two-component signaling. Using well-characterized examples, we speculate the circumstances in which each integration scheme confers a fitness advantage. Two-component systems allow bacteria to respond to specific environmental signals with defined adaptive phenotypic changes, a process that requires time and may be inadequate for contending with rapidly changing environments. In contrast, phase variation generates baseline levels of phenotypic heterogeneity that helps to ensure survival of the population as a whole. This strategy may be better suited to confront abrupt environmental changes but may produce transiently less-fit subpopulations. Many bacteria have integrated phase variation and two-component signaling – how combining these stochastic and deterministic mechanisms affects bacterial fitness is unclear. Here, we identify three distinct schemes for integration of phase variation and two-component signaling. Using well-characterized examples, we speculate the circumstances in which each integration scheme confers a fitness advantage.